ChemInform Abstract: Cyanoacetylation of Amines: Recent Advances in Preparation Methods and Their Synthetic Uses in the Formation of Biologically Active Compounds. Issue 17 (April 2016) - Fadda, Ahmed A.; Rabie, Ramy
Abstract: Review: 129 refs.